2011
DOI: 10.12968/ijtr.2011.18.7.392
|View full text |Cite
|
Sign up to set email alerts
|

Video conferencing us talking face-to-face: is video suitable for supportive dialogue?

Abstract: Aims: This study aimed to explore the differences between conversations carried out face-to-face and those via video link, to see if the latter was suitable for supporting health care students. The study's objectives were: to determine perceived differences between supportive conversations conducted via video link and those carried out face-to-face; and to explore potential causes of any perceived differences between the two methods of conversation. Methods: The study used a mix of methods including dialogue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Support for learning and assessment was also stressed, but contrasting information relating to the face-to-face visit activities undertaken (Table 1) suggested that different approaches could be used effectively. It is proposed that good pre-placement preparation for both students and educators allowed HEIs to reduce their input into problem solving and assessment during the face-to-face visit (Table 2), which, it could be argued, adds to the HEI debate relating to the value for money of current visiting practice [6] and [7].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Support for learning and assessment was also stressed, but contrasting information relating to the face-to-face visit activities undertaken (Table 1) suggested that different approaches could be used effectively. It is proposed that good pre-placement preparation for both students and educators allowed HEIs to reduce their input into problem solving and assessment during the face-to-face visit (Table 2), which, it could be argued, adds to the HEI debate relating to the value for money of current visiting practice [6] and [7].…”
Section: Resultsmentioning
confidence: 99%
“…As a good proportion of HEIs were happy to entrust the clinical educator with developing student problem solving and evaluating their achievement in relation to clinical assessment, there could be scope to support a move to more cost-effective alternative technological approaches such as video conferencing [6] and [8]. In this scenario, a lecturer or personal tutor visit to the placement would only be indicated should emotive issues become apparent, to provide appropriate pastoral support, or in the case of the student at risk of poor achievement or failure of placement objectives.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations